Loss of Guide Wire as an Important Complication of Central Venous Catheterization; a Case Report - Najari, Fares; Amirian, Mohamadjavad; Sadjadi, Sara; Baradaran Kayal, Ideh (Archives of Academic Emergency Medicine, 2018)
Many critically ill patients need aggressive procedures, such as central venous catheterization. The complication rate of central venous line placement is estimated to be 15%. Common complications include arterial puncture, hematoma, pneumothorax, hemothorax, arrhythmia, thoracic duct injury, infection, and thrombosis. Cardiac tamponade, pericardial effusions, pleural effusions, air or guidewire embolisms, and lost guide wires are rare but severe complications. Here we report a case of lost guide wire following central venous line insertion.